Deleterious effect of chronic continuous hypoxia on oral health - Terrizzi, Antonela Romina (2016)
Objective: To evaluate the effect of chronic continuous hypoxia (CCH) in alveolar bone and its correlation with the inflammatory markers which play a key role in the development of periodontitis. Material and methods: Wistar rats were exposed to CCH (600 mbar, 3 months). Macroscopic and histological analyses of alveolar bone were performed, together with measurement of oxidative stress and inflammatory parameters in gums and submandibular glands (SMG). Results: HCC induced cortical alveolar bone loss, decreased interradicular bone volume and increased the periodontal ligament height compared to control rats (p < 0.05). CCH enhanced iNOS activity in gums (from 2735,04 ± 662,96 nmol/min/mg proteins to 4289,58 ± 915,63 p < 0.05) and in SMG (from 56,71 ± 12,05 nmol/min/mg proteins to 90,15 ± 21,78 p < 0.05). PGE2 did not change in gums or in SMG by means of CCH, while TNFα decreased in gums (p < 0.05). Regarding oxidative stress, thiobarbituric acid reactive species concentration in CCH animals was higher both in gums as in SMG, and catalase activity was decreased in SMG. Conclusion: Higher iNOS activity both in gums and SMG under CCH could be associated with the alveolar bone loss observed. The increase in oxidative stress occurring in SMG and gums, together with a lower antioxidant capacity might indicate a deleterious effect of HX in oral health.